Cell biology and physiology of astroglia - Verkhratsky, Alexei (Henry Stewart Talks, 2011)
Astrocytes, Functions of astroglia, Adult neurogenesis, The functional architecture of grey matter, The blood-brain barrier and astrocytes, Astroglial perivascular processes, Mechanisms of molecular traffic through the blood-brain barrier, Controlling microcirculation, Metabolic support of neuronal networks, Brain energetics, The lactate shuffle, Homeostatic function, Water movements, Signalling function, Astroglia in synaptic transmission, Astrocytes as secretory cells, Distal signalling through the release of gliotransmitters
Archived at 2022/04/28